Empowering Women Post-Migrant Workers in Strengthening Family Economic Resilience (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2021)
This study aims to explore the empowerment potential for women in Mantren Hamlet, Bader Village, Dolopo District, Madiun Regency by utilizing parts of the teak tree to strengthen the family's economic resilience. Most women in Mantren are former migrant workers who are empowered to increase their income by processing young teak leaves. The method used in this research is the ABCD (Asset-Based Community-Driven Development) by using Christopher Dureau's theoretical approach. The empowerment mechanism used discovery, dream, design, and destiny also called a 4-D model or cycle. The researcher accompanies community empowerment by processing young teak leaves into tea bags and chips with this method. The findings show that women's economic resilience in Dusun Mantren is included in the low scale. Therefore, to improve the economic welfare of women in Dusun Mantren, the empowerment strategy used is to provide training and assistance in processing young teak leaves into teabags and chips so that they have high selling power. The products created in teabags and chips can help support the family's economic resilience for women who have retired as migrant workers.